The Development of Eco-Friendly Calligraphy Artwork Using Rice Husk Paper and Eggshell Materials at El-Ka Lampung Calligraphy Studio - Zarnuji, Ahmad; Eka Prasetiawati; Isnaini Nur Azizah; Hanif Amrulloh; Muhammad Nur Amin; Suhono, Suhono; Nur Khotimah; Aliya Nabila Sari (Yayasan Payungi Smart Madani, 2023)
Indonesia generates significant quantities of agricultural waste, including eggshells and rice husks, which often remain underutilized. This research-based community service project explores the innovative reuse of these materials—particularly rice husks—as eco-friendly components in the creation of calligraphy artworks. The objectives of the initiative were twofold: (1) to introduce and highlight the potential of eggshells and rice husks as sustainable, alternative materials for calligraphic art; and (2) to provide hands-on training on the practical techniques of producing calligraphy using eggshell fragments and rice husk-based paper. Utilizing the Asset-Based Community Development (ABCD) approach, the project actively involved the El-Ka Lampung Calligraphy Studio community in Metro City, Lampung. The outcomes of the initiative included the successful production of calligraphy pieces that exhibited both aesthetic appeal and distinctive textures resulting from the incorporation of organic materials. Moreover, the project fostered greater community awareness of environmentally sustainable art practices and enhanced participants’ skills in utilizing local waste products creatively. This initiative demonstrates how integrating traditional art with ecological awareness can empower communities and promote sustainable cultural innovation.